Rancangan Customer Relationship Management (CRM) Pada Layanan Laundry - Ayu Lestari; Eva Faja Ripantia; Hengky Anra (PT. Saha Kreasi Indonesia, 2025)
This research aims to design a web-based Customer Relationship Management (CRM) system for laundry services to improve operational efficiency and build long-term relationships between laundry owners and customers. This system integrates three main CRM phases: Acquisition, Retention, and Penetration. In the Acquisition phase, the website provides features for customer registration, easy registration, and promotions and discount vouchers for new customers. The Retention phase includes transaction history features, a loyalty program with discounts for frequent customers, and promotional notifications. The Penetration phase aims to offer additional services (cross-selling and up-selling) and provide notifications or discount vouchers to existing customers who have not yet used the new service. The system was built using the Waterfall method, which consists of requirements analysis, design, implementation, and testing. System testing using Black-Box Testing and User Acceptance Testing (UAT) showed satisfactory results, with satisfaction levels reaching 81.5% for admins and 90.4% for customers. These results demonstrate that this web-based CRM system is effective in improving user experience, operational efficiency, and building better relationships with customers to support sustainable laundry business growth.